Environmental management accounting and green practices as drivers of SME performance: evidence from an emerging economy - Solovida, Grace Tianna; Izzaty, Khairina Nur; Nugraha, Sendhy Ichza (LPPM ISNJ Bengkalis, 2025)
Purpose – This study investigates the impact of environmental management accounting (EMA) on financial performance (FP), with environmental management practices (EMP) and operational performance (OP) serving as mediating variables. Method – This study used a quantitative survey approach; data were collected from 98 managers or owners of green SMEs in Central Java, Indonesia. Data collection used a structured questionnaire with snowball sampling due to the lack of an official database of green SMEs in the region. Data was analyzed using SEM-PLS via SmartPLS software. Findings – The results show that environmental management accounting (EMA) positively influences environmental management practices (EMP). However, environmental management practices (EMP) do not influence operational performance (OP), whereas operational performance (OP) positively influences financial performance (FP). Additionally, environmental management practices (EMP) cannot mediate the relationship between environmental management accounting (EMA) and operational performance (OP); operational performance (OP) also cannot mediate the link between environmental management practices (EMP) and financial performance (FP). Implications – This study contributes to literature by underscoring the limited mediating role of environmental management practices in green SMEs and the challenges in converting environmental initiatives into operational gains. The findings suggest that SMEs should better integrate environmental accounting with operational strategies to enhance financial outcomes. Policymakers should also support SMEs through improved access to environmental management training and resources.